Red Perovskite Light‐Emitting Diodes: Recent Advances and Perspectives - Yu, Yi; Tang, Yingyi; Wang, Bingfeng; Zhang, Kai; Tang, Jian‐Xin; Li, Yan‐Qing (Laser & photonics reviews, 2023)
Metal halide perovskite (MHP) materials have shown great advantages for the next‐generation optoelectronic devices, especially for light‐emitting diodes (LEDs), on account of their outstanding photoelectric properties and facile solution processability. However, the performances of red perovskite LEDs (PeLEDs) are not ready for commercialization, presumably due to the instability both of the emission spectra and operation conditions, and the toxicity of lead ions. In this review, the structures, physical properties, and preparation approaches of red emissive perovskite materials are first introduced, including 3D bulk perovskites, 2D and quasi‐2D perovskites, and colloidal perovskite nanocrystals (NCs). In addition, several strategies that contribute to the recent development and achievement of red PeLEDs are summarized in detail, mainly involving component engineering, dimension, and phase distribution modulation, ligand engineering, additive engineering, interfacial engineering, and strategies for the light out‐coupling device structure. Moreover, the challenges and corresponding solutions are discussed from three aspects of spectral stability, operational stability, and lead‐free red PeLEDs. Finally, the conclusion and outlook on the promising future of the red PeLEDs are raised. Recent advances and in red‐emissive perovskite light‐emitting diodes are reviewed in terms of red emitters, device structures, spectral and operational stability. The strategies to optimize the device performance are highlighted, involving component engineering, dimension and phase distribution modulation, ligand engineering, additive engineering, interfacial engineering, and light out‐coupling structures.